TINGKAT KEPUASAN KHALAYAK KOTA PEKANBARU DALAM MENONTON PROGRAM BERITA “DETAK RIAU MALAM” PADA STASIUN TELEVISI LOKAL RIAU TELEVISI (RTV) - Ananda, Nadia; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Mass media, especially television, has become an option for the public to get information. The existence of various television channels makes people have many choices to watch quality shows. In the Uses and Gratification theory, audiences use mass media based on certain motives where the media try to meet the needs and satisfaction of the audience. To determine audience satisfaction by measuring satisfaction sought when watching (sought gratification) and satisfaction after watching television (obtained gratification). The purpose of this study is to find out how much satisfaction the audience of Pekanbaru City in watching the news program "Detak Riau Malam" on the local television station Riau Television (Rtv).This study uses a quantitative descriptive approach. The location of this research is Pekanbaru City, Riau. Sampling was done by accidental sampling with the unknown population formula and obtained a sample of 166 respondents. The researcher used a comparison of the mean to see whether the program "Detak Riau Malam" fulfilled the satisfaction of the audience in Pekanbaru City. While for processing the questionnaire data, it is done by using the Windows version 23 Statistical Of Service Solution (SPSS) Program.The results of this study indicate that the mean motive of watching the program "Detak Riau Malam" (sought gratification) of 2.975 is in the high range where there are differences in the mean value of Gratification Obtained (3.07). It can be concluded that the detak riau malam program can meet the expectations of the Pekanbaru City audience in watching news with GS <GO.Keyword : Local Television, Satisfaction Level, Riau Television